1987
DOI: 10.1148/radiology.165.1.3498184
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cerebral perfusion after acute head injury: comparison of CT with Tc-99m HM-PAO SPECT.

Abstract: Technetium-99m hexamethylpropyleneamine oxime (Tc-99m HM-PAO) was successfully used with single photon emission computed tomography (SPECT) on fourteen comatose patients who had acute head injuries. The SPECT scans were correlated with computed tomography (CT) scans obtained within 24 hours of the injury. Tc-99m HM-PAO SPECT was shown to have the following advantages: It reflected perfusion changes, was more sensitive than CT in demonstrating more lesions, and demonstrated lesions at an earlier stage than thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Early landmarks in SPECT research were made by studies that reported findings on patient groups without reference to a control group [Abdul-Dayem et al, 1987;Ryding et al, 1988;Shen et al, 1990;Denays et al, 1990;Holman et al, 1991;Tumeh et al, 1990;Berman et al, 1987]. Other seminal studies used controls without reference to gender or age [Costa et al, 1988;Holman et al, 1991], or they compared patient groups to one another.…”
Section: Methodsmentioning
confidence: 99%
“…Early landmarks in SPECT research were made by studies that reported findings on patient groups without reference to a control group [Abdul-Dayem et al, 1987;Ryding et al, 1988;Shen et al, 1990;Denays et al, 1990;Holman et al, 1991;Tumeh et al, 1990;Berman et al, 1987]. Other seminal studies used controls without reference to gender or age [Costa et al, 1988;Holman et al, 1991], or they compared patient groups to one another.…”
Section: Methodsmentioning
confidence: 99%
“…It was shown that SPECT detected 40% more lesions than shown by CT scans (65). Similar results have been reported by Roper et al (66).…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…[3][4][5][6][7] However, it should be noted that "MRI sequences," new and complicated techniques for improving neuroimaging quality, may alter this conclusion in the future, although we could find no published studies that have directly compared MRI sequences to SPECT. SPECT scans were ordered only for patients in whom documentation of hypoperfusion and functional deficits might be helpful in clarifying diagnoses and treatment planning.…”
Section: Review Of Two Years Of Experiences With Spect Among Psychiatmentioning
confidence: 99%